O estudo da amalgama na obra Arte de los metales de Álvaro Alonso Barba e sua contribuição para o desenvolvimento da mineração na América - Oliveira, Antonio Rodrigues de (2009)
This dissertation is related to the analysis of the work De Los Metales Art and its influence in improving the knowledge of mineralogy and metallurgy. As the original Spanish, this work was translated by us, based on terms used in mining at the end of the sixteenth century and early seventeenth century. This work highlighted by the disclosure and publication in several languages, bringing an improvement and development in the metallurgy, in all countries working with mining of gold and silver. With it, the newly discovered American colonies also have great influence, because at the time were the largest suppliers of gold and silver to European countries. Written by Álvaro Alonso Barba, established some relationships between texts of previous mining and contemporary to it, since he came to explain and improve points until then were not very clear. We talk about the technical work Barba, showing the improvement he succeeded in mining and in favor of silver, with greater recovery and less expense. Some aspects of social problems, political and financial that occurred between the Spanish colonies and Spain at the end of the sixteenth century are also studied with the aim of showing the environment in which this work was produced and to check its influence